2020
DOI: 10.1098/rsob.200116
|View full text |Cite
|
Sign up to set email alerts
|

An miRNA fingerprint using neural-enriched extracellular vesicles from blood plasma: towards a biomarker for amyotrophic lateral sclerosis/motor neuron disease

Abstract: Biomarkers for amyotrophic lateral sclerosis/motor neuron disease (ALS/MND) are currently not clinically available for disease diagnosis or analysis of disease progression. If identified, biomarkers could improve patient outcomes by enabling early intervention and assist in the determination of treatment efficacy. We hypothesized that neural-enriched extracellular vesicles could provide microRNA (miRNA) fingerprints with unequivocal signatures of neurodegeneration. Using blood plasma from ALS/MND patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
73
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(74 citation statements)
references
References 94 publications
(136 reference statements)
1
73
0
Order By: Relevance
“…Mir-199a has been described dyseregulated during microglial hyper-activation and persistent neuroinflammation, two abnormal conditions that support pathogenensis of ALS. In addition miR-151a-5p is thought to participate in the maintenance of cell viability in response to oxidative stress, its expression levels increased in the spinal cord of ALS patients, and it has been used as a non-muscle therapeutic target in ALS SOD1 G93A mouse models 13,29 . Interestingly, we observed the up-regulation of miR-151a-5p in the early phases of the disease and its significant down-modulation in the latest one, suggesting its involvement in the initial cell attempts to counteract disease onset and progression.…”
Section: Discussionmentioning
confidence: 99%
“…Mir-199a has been described dyseregulated during microglial hyper-activation and persistent neuroinflammation, two abnormal conditions that support pathogenensis of ALS. In addition miR-151a-5p is thought to participate in the maintenance of cell viability in response to oxidative stress, its expression levels increased in the spinal cord of ALS patients, and it has been used as a non-muscle therapeutic target in ALS SOD1 G93A mouse models 13,29 . Interestingly, we observed the up-regulation of miR-151a-5p in the early phases of the disease and its significant down-modulation in the latest one, suggesting its involvement in the initial cell attempts to counteract disease onset and progression.…”
Section: Discussionmentioning
confidence: 99%
“…Huntington's disease Alzheimer's disease Parkinson's disease Amyotrophic lateral sclerosis "Non-specific" exosomes Absence of mHTT (Denis et al, 2018) Phosphorylated tau (Saman et al, 2012) ↓REST (Goetzl et al, 2015) ↑miR195 and miR24 ↓miR19b (Cao et al, 2017) Altered levels of miRNA (Yelick et al, 2020) NDEs ↑AÎČ1-42 ↓Synaptic proteins ↑TDP43 (Fiandaca et al, 2015;Goetzl et al, 2016Goetzl et al, , 2018Zhang et al, 2020) ↓synaptophysin, synaptotagmin and SNAP-25 (Goetzl et al, 2016;Agliardi et al, 2019) ↓miR132 and miR-212 (Walsh et al, 2019) ↑DJ1 and α-synuclein (Zhao et al, 2019) ↑α-synuclein and clusterin (Jiang et al, 2020) ↑α-synuclein (Shi et al, 2014;Jiang et al, 2020;Fu et al, 2020;Niu et al, 2020) Altered levels of miRNA (Katsu et al, 2019;Banack et al, 2020) NDEs, neuronally derived exosomes; mHTT, mutant huntingtin; REST, repressor element 1-silencing transcription factor; AÎČ1-42, amyloid beta-42; TDP43, TAR DNAbinding protein 43; SNAP-25, 25 kD synaptosomal protein; miR, micro RNA.…”
Section: Exosome Sourcementioning
confidence: 99%
“…The identification of miRNA (e.g., miR-124-3p, hsa-miR-4736, and miR-146a-5p) with altered levels in both neuronal-derived and total exosomes from ALS patients (CSF and plasma) gave some insight into novel targets to overcome the pathology ( Table 1 ; Banack et al, 2020 ). Nonetheless, the research regarding the role of exosome vesicles in ALS has still a long way to go to allow a better understanding of how we can use the already acquired knowledge to mitigate the progression of these neurodegenerative processes.…”
Section: Critical Roles Of Exosomes In Neurological Disordersmentioning
confidence: 99%
“…For instance, in a recent study by Ebrahimkhani S. et al, the utility of serum exosome miRs as disease biomarkers of MS patients under treatment with fingolimod was assessed, and they found that several combinations of two or three miRNAs could discriminate active from quiescent disease with more than 90% accuracy [ 79 ]. Likewise, for ALS, Banack et al found that eight miRNAs, isolated from neural-enriched EVs, significantly distinguished ALS patients from controls, and thus might assist in early diagnosis of this disease [ 75 ].…”
Section: Central Nervous System Disease-related Biomarkers In Extrmentioning
confidence: 99%